Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Indigenous Knowledge of Namibia 2015
DOI: 10.2307/j.ctvgc619h.11
|View full text |Cite
|
Sign up to set email alerts
|

School learners’ knowledge and views of traditional medicinal plant use in two regions in Namibia

Abstract: Local knowledge about natural resources that may be of use to communities, including medicinal plants, is becoming increasingly important globally. This knowledge is important for the participation of indigenous peoples in the conservation and maintenance of indigenous forests (Gazzaneo, de Lucena, & de Albuquerque, 2005) in addition to the frequent use of these resources in the treatment of common ailments and diseases.Knowledge about the use of local fauna and flora, nowadays, is minimal. To ensure the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The extracts and compounds exhibited activities with IC 50 values, ranging from 31.4 µg/mL to 80.2 µg/mL, which was comparable to IC 50 value of 48.9 µg/mL exhibited by quercetin, the control [46]. These findings support the traditional use of the species as herbal medicine for abdominal pains [24], body pains [20], skin inflammations [19,20,30,31,32], and wounds [51].…”
Section: Pharmacological Activitiessupporting
confidence: 59%
See 1 more Smart Citation
“…The extracts and compounds exhibited activities with IC 50 values, ranging from 31.4 µg/mL to 80.2 µg/mL, which was comparable to IC 50 value of 48.9 µg/mL exhibited by quercetin, the control [46]. These findings support the traditional use of the species as herbal medicine for abdominal pains [24], body pains [20], skin inflammations [19,20,30,31,32], and wounds [51].…”
Section: Pharmacological Activitiessupporting
confidence: 59%
“…The extract and the compounds demonstrated moderate antibacterial activities with MIC values ranging from 0.1 mg/mL to 1.7 mg/mL [54]. These findings corroborate the traditional use of the species as a herbal medicine for diarrhoea [10,18,19,20,21,22,23], sexually transmitted infections [16,35,45,46,50], skin infections [19,20,30,31,32], sore throat [32], stomach aches [19,20,21,22,23,26,27,28,29], venereal diseases [22,38], and wounds [51].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Further, she argues that Namibian teachers emphasize procedural thinking and rote learning. Likewise, Kapenda et al (2015) also argues that Namibian mathematics teachers chose to develop procedural mathematics skills compared to conceptual understanding. A study by Miranda and Adler (2010) found that Namibian teachers did not use manipulatives during lessons.…”
Section: Previous Researchmentioning
confidence: 99%
“…The study recommended a complementary course in mathematics for these teachers. Research (see N. Feza, 2014;Kapenda et al, 2015) has argued that teachers who lack appropriate pedagogical and subject content knowledge negatively affect the extent to which their learners can learn.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation